An Analysis of Personality (Introvert, Extrovert, and Ambivert) Students’ Learning Styles in English Learning Process at the 11th Grade of SMKN 1 Bukittinggi - Putri Indriani; Veni Roza; reflindareflinda; Widya Syafitri (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study was due to the high number of students, particularly in the 11th grade, who are not yet aware of their own personalities and learning styles. Students tend to follow the learning process as directed by their teachers, while teachers predominantly use traditional methods with limited variations in the classroom. Consequently, students whose personalities did not align with these methods may struggle to engage effectively in the learning process. This study used a descriptive quantitative research approach with descriptive statistical methods. The population in this research consists of 11th-grade students at SMKN 1 Bukittinggi. The sample for the study was selected using a random sampling technique, resulting in a randomly chosen group of 11th-grade students. The instruments used in the study include questionnaires to investigate learning styles and another set of questionnaires to assess personality types. For data analysis, the researchers applied descriptive statistics with percentages and data visualizations, representing the results in bar and pie charts. The results revealed that the dominant personality type among 11th-grade students at SMKN 1 Bukittinggi is ambivert, accounting for 64% of the total sample. The dominant learning style among these students is kinesthetic, with a total percentage of 26%. The study also found that the dominant learning style for introverted students is visual, while extroverted students primarily prefer kinesthetic learning. Meanwhile, ambivert students tend to prefer a multimodal approach, showing the ability to adapt to various learning styles.